FAMILY PLANNING SERVICES AT DENPASAR TOWARD A HEALTHY CITY - Luh Seri Ani; I Made Merdana; Nyoman Sumiati (Jurnal Pengembangan Kota, 2019)
One of the goals of urban development is to improve the quality of life of the people, especially in the aspect of health, as found in Denpasar, Bali, which wants to create a healthy city. Denpasar City Development is expected to create and improve health services for the entire community. Improved health infrastructure services are expected to support other government health programs, including the Family Planning Program (KB) as an effort to inhibit the rate of population growth that negatively impacts the economy and environment of a rural and urban area. Through family planning programs people can set the number of children and the desired pregnancy distance, especially for people who live in urban areas. This study aimed to determine contraceptive services in Fertile Age Women (WRA) in urban areas. A cross-sectional descriptive survey was conducted on 1,777 women of childbearing age in Denpasar City. Data on family planning users were obtained from the BKKBN family data collection in 2018. The survey data were processed through univariate and bivariate analysis to determine trends in the use of contraceptives in Denpasar. 55.7% of family planning services in Denpasar are in a bad category. Fertile Age Women (WUS) in the city of Denpasar do not have health insurance (41.6%), do not receive family planning information through the media (41.1%), do not get information from health workers (73.5%), do not get field visit from the health workers ( 96.5%) and do not receive counseling services (59.8%). The low utilization of family planning services will affect the quality of life of the community in Denpasar, especially the WUS, and become a barrier to achieve a healthy city.